Profit Management and Islamic Business Ethics - Budiman Budiman (UIN Sunan Gunung Djati Bandung, 2020)
Financial reports are important elements in economics, so that a rule is formed in the financial reporting process called General Accepted Accounting Principles (GAAP). The aim is to unify financial reporting and financial reporting for each business entity in a country to facilitate the auditing process for fairness in reporting. This study will discuss earnings management in terms of Islamic ethics. The research method uses the literature review method concerning Islam's references and matters relating to profit management and Islamic business ethics. In this study, it can be seen that the behavior of a manager towards profit management by manipulating profit figures on paper is not following what is instructed by Islamic teachings and the basic laws of various types of muamalah are permissible until arguments are found that prohibit them.